The Role of the Literary and Social Protest in the selected Novels of John Steinbeck in the Global Supply Chain - Rasha Hassooni Abdullah (International Journal of Supply Chain Management, 2018)
Let us rise up tonight with a greater readiness. Let us stand with a greater determination. And let us move on in these powerful days, these days of challenge to make America what it ought to be. We have an opportunity to make America a better nation. (Martin Luther King, Jr.1). The notion of "literature of protest" in the global supply chain has different interpretations by different people. For the social and historical critics literary reformative calls ought to have a specific political objective, like changing a regime. From the deconstructionists viewpoint the literary text is ultimately a kind of protest in the global supply chain, meanwhile for a Marxist literary protest has to stir up and repeat the order of the relationships among the layers of the society. A feminist critic could claim that protest in the global supply chain does or does not promote a gender prejudice and a psychologist might think of it as exhibitions of the subconscious. Social calls for reforms may take an altogether new form for a traditional literary, critics who might argue that the moral connection between aesthetics and the political content is the content of the literature of societal protest in the global supply chain. Protest Literature in the global supply chain has existed in different forms throughout the literary history. Many of the important writers over the ages have utilized their expertise to awakening the societies to injustices locally and universally. They have in its spectrum some of the most instigating thoughts to provoke the emotions, besides such writings on the struggle of the individuals against social injustice. In other words protest art is the art that concentrates on disavowing the society's drawbacks and art that either supports or opposes some types of political or social amendments.